2012
DOI: 10.1186/1472-6882-12-62
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention with narrow-leaved cattail rhizome flour (Typha angustifolia L.) prevents intestinal inflammation in the trinitrobenzenesulphonic acid model of rat colitis

Abstract: BackgroundInflammatory bowel disease (IBD) is a chronic inflammation of the intestinal epithelium that is driven by the intestinal immune system, oxidative stress and the loss of tolerance to the luminal microbiota. The use of dietary products containing ingredients such as fibres and carbohydrates and/or antioxidant compounds have been used as a therapeutic strategy for intestinal diseases because these products are considered effective in the modulation of the immune system and colonic microbiota. We investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Typha rhizomes present a wide variety of chemical compounds, among them saponins, coumarins and flavonoids (Fruet et al, 2012). The compounds typhaphthalide, typharin, sitosterol, afzelechin, epiafzelechin, (+)-catechin, and (-)-epicatechin were also isolated and identified from rhizomes of Typha capensis Rohrb.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typha rhizomes present a wide variety of chemical compounds, among them saponins, coumarins and flavonoids (Fruet et al, 2012). The compounds typhaphthalide, typharin, sitosterol, afzelechin, epiafzelechin, (+)-catechin, and (-)-epicatechin were also isolated and identified from rhizomes of Typha capensis Rohrb.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Typha species are widely used as medicinal plants (Fruet et al, 2012). In a recent study, Fruet et al (2012) reported that rhizome flour from T. angustifolia displays significant antioxidant activity.…”
Section: Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…97 More recently, narrow-leaved cattail (Typha angustifolia L.) rhizome flour and green dwarf banana (Musa sp.AAA) flour both were found to decrease colonic AP activity in a rat model of colitis. 98,99 Coumestrol, a phytoestrogen known to regulate intestinal calcium absorption, was found to inhibit IAP gene expression and enzyme activity, although differential regulation was evident in the duodenum and the jejunum in neonatal pups and lasted until 10 days postparturition. 100,101 It was suggested that estrogen receptor-alpha (ER-α) may be involved in this transient inhibition.…”
Section: Stimulation Of Iap By Various Plant Bioactive Compoundsmentioning
confidence: 99%
“…Considering prebiotics can be a source of SCFAs in the body, several dietary products rich in non-digestible components are potential candidates to treat or prevent chronical diseases such as diabetes, obesity, metabolic syndrome and inflammatory bowel disease. Based on this, our laboratory has been interested in studying the protective effects afforded by functional foods against intestinal inflammatory process (Fruet, Seito, Rall, & Di Stasi, 2012;Scarminio, Fruet, Witaicenis, Rall, & Di Stasi, 2012;Witaicenis, Fruet, Salem, & Di Stasi, 2010) with special interest in tropical foods, among which dwarf banana (Musa sp. AAA) was selected because its fruits in immature state are rich in dietary fibre and starch granules (Da Motta, Lajolo, Ciacco, & Cordenunsi, 2000).…”
Section: Introductionmentioning
confidence: 99%